Fear of Covid-19 and burnout among healthcare providers in Malaysia: Is resilience a missing link? - Ching, Siew-Mooi; Thurasamy, Ramayah; Cheong, Ai Theng; Yee, Anne; Lim, Poh Ying; Ismail, Irmi Zarina; Lee, Kai Wei; Ng, Jun Ying; Abdul Rahim, Rofina; Mohd Noor, Mohd Khairi; Cheng, Chang Li; Mohd Nazan, Ahmad Iqmer Nashriq; et al. (Universiti Putra Malaysia, 2023)
Introduction: During the COVID-19 pandemic, healthcare providers have been in great fear due to the high risk of contracting COVID-19 infection at any time. This study aimed to determine the mediating role of resilience on the relationship between fear of COVID-19 and burnout in primary care healthcare providers in Malaysia. Methods: This was an online cross-sectional study involving 1280 healthcare providers aged 18 years and older from 30 government primary care clinics in Malaysia. We used the COVID-19 Fear Scale, the Copenhagen Burnout Inventory Scale, and the Short Brief Resilience Scale to collect data from the respondents. Smart-PLS was used to perform mediation analysis. Results: The mean age of the respondents was 36 years old and mean duration of working experience was 11 years. The majority of the respondents were female (82.4%) and Malays (82.3%). The study population consisted of nurses (47.4%), doctors (26%), medical assistants (11.9), healthcare assistant (7.1%), medical laboratory technicians (6.4%) and drivers(1.3).The results show that fear of COVID-19 positively predicts burnout. According to the results, resilience mediates the relationship between fear of COVID-19 and all the three burnout domains, namely personal burnout (β=0.175,p<0.001), work-related burnout (β=0.175,p<0.001) and client-related burnout (β=0.172,p<0.001). Additionally, resilience reduces the impact of COVID-19 fear on the three domains of burnout. Conclusion: Our study has reported a mediating effect of resilience on the relationship between fear of COVID-19 and burnout.